Interference suppression for frequency-hopped multiple-access receiver - Chitra, Bhupathy (2018)
In this dissertation, frequency hopped multiple access system is studied. Frequency hopped spread spectrum is commonly used in military application which is quite sensitive to interference. In this dissertation, bit error rate performance results of Binary Frequency Shift Keying (BFSK), Fast Frequency Hopped/ Binary Frequency Shift Keying (FFH/BFSK) and Fast Frequency Hopped Multiple Access (FFH/MA) under Additive White Gaussian Noise (AWGN), Rician and Rayleigh channels are studied. It also focuses on both intentional interference and unintentional interference. Partial Band Noise Jamming (PBNJ) and Multiple Access Interference (MAI) are mainly considered and their effects are studied. To mitigate the effects, Maximum Likelihood (ML) receiver is used and its performance under fading and nonfading channels are studied. Bit error rate performance of Maximum likelihood receiver is compared with linear combining receiver which proves that the ML receiver is better in performance than the linear combining receiver. The performance-affecting factors such as number of users, fading channel, number of hops are also considered.